DEVELOPMENT OF DESIGN TECHNOLOGY FOR FUTURE VOCATIONAL EDUCATION TEACHERS, MODEL OF TRAINING AND BASIC INDICATORS OF DISSERTATION - MuslimovNarzullaAlikhanovich, Urazova Marina Batyro, MuslimovSherzodNarzullaugli vna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In our research, the designer acts as a future teacher who can only achieve positive results in the study of business style, the experience of mental actions, and experience of learning emotional-value relationships with reality. That is. is to study the experience of successful teaching activities of teachers. Hence, it is the design of the most specific aspects of learning to address specific problem-solving tasks, including designing, creating, constructing, and planning to achieve useful results in practice. Our curriculum described the types of educational activities that involved planning, organizing, and analyzing the learning process.